ПЕДАГОГІКА ШКІЛЬНОЇ КОМУНІКАЦІЇ І НАСИЛЬСТВО УЧНІВ У ШКОЛІ - Зубелевич, Я. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Можна вирізнити педагогіку консервативну (аксіоцентричну) та педагогіку пайдоцентричну. У пайдоцентризмі метою є стимулювання самореалізації дитини, а засобами для цього є її експресія, дуже обмежена дисципліна, права дітей. Академічна педагогіка в Польщі схвально ставтться до педагогіки пайдоцентричної. У Польщі за останні кільканадцять років насильство учнів над учителями стала серйозною освітньою та суспільною проблемою. Представники академічної педагогіки проявляють повну безпорадність у поданні причин насильства учнів над учителями. Та водночас характеризуються мегаломанією. Не дивлячись на певного роду безпорадність, вони вказують на деякі причини насильства. Загалом, головну вину вони покладають на вчителів, насамперед, – на їхні слабкі дидактичні компетентності та погані стосунки з учнями. Представники ж консервативної педагогіки головну причину насильства учнів над учителями вбачають у пропаганді принципів пайдоцентричної педагогіки. Ці [принципи] особливо проявляються у ліквідації дисципліни та інституціонального авторитету вчителя. Jan Zubelewicz. The pedagogic of school communication and students’ violence in the school. There is conservative (axiocentric) pedagogy and paedocentric pedagogy. The aim of paedocentrism is to stimulate the child’s self-realisation by means of their own expression, very limited discipline, children’s rights. Academic pedagogy in Poland takes a positive attitude towards paedocentric pedagogy. In recent years in Poland violence of students against teachers has become an important educational and social problem. Representatives of academic pedagogy show considerable vulnerability in defining the causes of students’ violence against teachers. At the same time, they are characterised by megalomania. Despite a kind of helplessness, they suggest some reasons of violence. In general, they blame mainly teachers, especially their weak didactic competence and poor relations with students. According to conservative pedagogy supporters, the main cause of students’ violence against teachers lies in promoting the paedocentric pedagogy principles. It is reflected in particular in abolishing discipline and the teacher’s institutional authority. Keywords: aksiocentrizm, paydocentrizm, pedagogics, communication, violence, megalomaniya.